2015
DOI: 10.5325/transportationj.54.4.0496
|View full text |Cite
|
Sign up to set email alerts
|

Inland Intermodal Terminals Location Criteria Evaluation: The Case of Croatia

Abstract: Determining a suitable location for an intermodal terminal is a critical element of the terminal establishment process, a decision on which the functionality of the entire intermodal freight distribution chain depends. The purpose of this article is to evaluate the criteria used for deciding on suitable locations for intermodal terminals in Croatia. First, quality indicators of intermodal terminals were identified: flexibility, safety and security, reliability, time, and accessibility. Based on these quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
0
33
0
1
Order By: Relevance
“…To a greater or lesser extent, several authors have addressed the issue of building intermodal transport terminals, for example, [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To a greater or lesser extent, several authors have addressed the issue of building intermodal transport terminals, for example, [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this process, it is necessary to make a number of decisions concerning the nodes in the network (LCs), allocation of users and flows to the network participants, transport modes and means, i.e., about all the factors that affect the network flows [37]. As some of the most important elements of the network, LCs are the subject of numerous studies related to their number and location (e.g., [38]), functions (e.g., [39,40]), connection possibilities (e.g., [41]). The existing literature also recognizes ambiguity on the conceptual boundaries of logistics centres [10].…”
Section: Intermodal Terminals As Nodes In the Logistics Networkmentioning
confidence: 99%
“…Without the constraint of space, the new inland terminals can also have co-located activities, such as storage, warehousing and business parks; for example, the Cube Business Park (2018) in Moorebank Intermodal Station and the Somerton Business Park (2018). Roso, Brnjac and Abramovic (2015) [7] showed that the key considerations in the selection of the site for a dry port terminal location are a good flow followed by a spatial criterion. In most cases, these new facilities must blend into the surrounding areas (Roso and Lumsden 2009) [5].…”
Section: What Are Dry Ports?mentioning
confidence: 99%